Manipulation of breather waves with split-dispersion cascaded fibers. (1st June 2022) - Deng, Zhixiang; Zhang, Jin; Fan, Dianyuan; Zhang, Lifu
Abstract: A stabilization scheme is proposed for the dynamics of breather waves induced by the coherent-seed modulation instability based on manipulation of phase-space trajectory. Theoretical and numerical analysis show that carefully dispersion- and nonlinearity-managed cascades of fiber configuration allows the system evolution to be stabilized around an elliptic center point, forming stable pulse trains with ultrahigh contrast efficiently. We also demonstrate that the scheme proposed works equally well for near-separatrix dynamics. Our results provide an alternative means to control the unsteady nonlinear waves by abruptly changing the waveguide properties.